The use of cash and the size of the shadow economy in Sweden - Gabriela Guibourg; Björn Segendorf (Sveriges Riksbank, 2007)
We use an 'unexplained demand for cash' approach to measure the size of the shadow economy in Sweden. The size of the shadow economy is found to have increased from 3.8 to 6.5 per cent of GDP from 1990 to 2004. This result is also supported by our finding of an increased residual between households' recorded disposable income and their consumption, investments and changes in net financial positions. Moreover, the correlation between the demand for cash that cannot be explained by recorded transactions and this residual is strong.
Keywords: E41; E26; H26; 330; Cash use; demand for cash; shadow economy; National Accounts; Financial Accounts; Bargeld; Schattenwirtschaft; Haushaltseinkommen; Konsumentenverhalten; Schweden